8-HQCdCl2H2O as an organic Q-switcher in erbium laser cavity* - Mohammed Najm, Mustafa; Abdullah, Mohammed Najm; Almukhtar, Aya A.; Hamida, Belal Ahmed; Yasin, Moh; Harun, Sulaiman Wadi (Springer Nature, 2023)
This paper demonstrated a Q-switched erbium-doped fiber laser (EDFL) using an organic saturable absorber (SA) based on 8-HQCdCl2H2O material. The organic thin film was prepared using the casting process. The proposed Q-switched EDFL has a maximum repetition rate of 143 kHz, minimum pulse duration of 1.85 µs and the highest pulse energy of 167 nJ. The Q-switched peak laser was at a central wavelength of 1 531 nm with a 3 dB bandwidth of 3.52 nm and power intensity of 2.64 dBm.